Are Expert Patients an Untapped Resource for ART Provision in Sub-Saharan Africa?. (19th April 2012) - Decroo, Tom; Van Damme, Wim; Kegels, Guy; Remartinez, Daniel; Rasschaert, Freya
Abstract : Since the introduction of antiretroviral treatment, HIV/AIDS can be framed as a chronic lifelong condition, requiring lifelong adherence to medication. Reinforcement of self-management through information, acquisition of problem solving skills, motivation, and peer support is expected to allow PLWHA to become involved as expert patients in the care management and to decrease the dependency on scarce skilled medical staff. We developed a conceptual framework to analyse how PLWHA can become expert patients and performed a literature review on involvement of PLWHA as expert patients in ART provision in Sub-Saharan Africa. This paper revealed two published examples: one on trained PLWHA in Kenya and another on self-formed peer groups in Mozambique. Both programs fit the concept of the expert patient and describe how community-embedded ART programs can be effective and improve the accessibility and affordability of ART. Using their day-to-day experience of living with HIV, expert patients are able to provide better fitting solutions to practical and psychosocial barriers to adherence. There is a need for careful design of models in which expert patients are involved in essential care functions, capacitated, and empowered to manage their condition and support fellow peers, as an untapped resource to control HIV/AIDS.